Ecolexicon of Kaghati Kolope Body Parts in Muna Speech Community - Nirmalasari Nirmalasari; Aron Meko Mbete; I Wayan Simpen; Anak Agung Putu Putra (Soshum: Jurnal Sosial dan Humaniora, 2018)
This article explained the ecolexicon of kaghati kolope body parts in Muna Speech Community (MSC). The kite ‘kaghati’ is one type of the traditional games and a tribal cultural product in MSC which still exists and remains maintained. MSC named the kite as kaghati kolope because the kite’s wall is made from gadung leaf or in Muna language called roo kolope. The aim of this research is to describe the body parts of kaghati kolope from the ecolingustic perspective. This research is classified as a qualitative descriptive study as it describes the phenomena of kaghati body parts and environmental knowledge, especially the ones currently used in ke-kaghati-an’s environment, and the source of natural data as a manifestation of the Muna's socio-cultural-ecological life. Based on the results of data analysis is found thirteen ecolexicon of kaghati kolope body parts. The ecolexicon is included in an abiotic group consisting of basic and complex words as noun categories. The ecolexicon of kaghati kolope body parts found in ke-kaghati-an environment such as ghurame, kaindere, kalolonda, kamuu, kasaa, kapongke, kaworu, kasamba, pani, padhi, kasoma, roo kolope, and kopu-kopunda.The ecolexicon is used in the making of kaghati kolope is meaningful and referential, i.e the lexicon whose references can be clearly seen, proven, both empirically and visible because it is found in the field or is still remembered by the speaker.